Can Government Policies Drive Open Innovation Type Platforms? Ideas from the MSC Malaysia Flagship Applications. (November 2017) - Omar, Aliza A.; Mohan, Avvari V.; ZHAO, XIAOFEI
The discussion of open innovation has always been centred on the organisation where innovation occurs. The focus would be on the inflow and outflow of knowledge into the organisation; several studies and cases published have addressed the concept around business (or government) organisations and their research and development (R&D) activities. The open innovation framework is based on a focal organisation, which is usually a business organisation that provides a platform for other organisations to collaborate—either helping the focal organisation to commercialise its knowledge and gain economic benefits or vice versa. This notion, we argue, is where an open innovation platform is 'supplier-driven', that is, 'supplier' indicating the focal organisation where innovation occurs. In this article, however, we propose an alternate framework for open innovation, that is, one that is 'customer-driven' where the customer organisation or demand-creating organisation provides a platform for open innovation. This alternate notion is derived from the case of the flagship applications of Malaysia's Multimedia Super Corridor (MSC Malaysia). The MSC Malaysia flagships can be seen as open innovation type platforms established by the customer, that is, the Malaysian government—which provides the demand pull for creating an open-innovation platform. This framework of a 'customer-driven' open innovation platform could provide lessons for other emerging economies to understand how their governments can play a more active role, as policymaker and demand-generating entity, to create a platform for open innovation.